2013
DOI: 10.1186/2045-709x-21-25
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary chiropractic practice in the UK: a field study of a chiropractor and his patients in a suburban chiropractic clinic

Abstract: Background: Two recent surveys of chiropractors in Great Britain suggest that there are discrepancies between chiropractic practice as defined in regulatory guidelines and day-to-day chiropractic clinical practice and there is in general a paucity of information regarding the characteristics of contemporary chiropractic practice in the United Kingdom. This field study describes the daily practice of a contemporary British UK-trained chiropractor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…(2012) [ 24 ] UK Forming connections in the homeopathic consultation homeopathy Practice wisdom, patients’ narratives, biomedicine, intuition Relate, diagnose and treat, legitimise Qualitative, data collected via interviews, observations and practitioner diaries, grounded theory 29 Eyles, C. et al (2011) [ 25 ] A grounded theory study of homeopathic practitioners’ perceptions and experiences of the homeopathic consultation 26 6 Fortune, L. D. & Hymel, G. M. (2015) [ 26 ] USA Creating integrative work: a qualitative study of how massage therapists work with existing clients massage therapy Practice wisdom, intuition, biomedicine, formal education and training, patients’ narratives Relate, diagnose and treat Qualitative, ethnomethodology, hermeneutic phenomenology 28 7 Hennius, B. J. (2013) [ 27 ] UK Contemporary chiropractic practice in the UK: a field study of a chiropractor and his patients in a suburban chiropractic clinic chiropractic Patients’ narratives, traditional knowledge, patients’ bodies, intuition, biomedicine Diagnose and treat, legitimise, educate and inform Ethnography 29 8 Ho, E.Y. & Bylund, C.L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012) [ 24 ] UK Forming connections in the homeopathic consultation homeopathy Practice wisdom, patients’ narratives, biomedicine, intuition Relate, diagnose and treat, legitimise Qualitative, data collected via interviews, observations and practitioner diaries, grounded theory 29 Eyles, C. et al (2011) [ 25 ] A grounded theory study of homeopathic practitioners’ perceptions and experiences of the homeopathic consultation 26 6 Fortune, L. D. & Hymel, G. M. (2015) [ 26 ] USA Creating integrative work: a qualitative study of how massage therapists work with existing clients massage therapy Practice wisdom, intuition, biomedicine, formal education and training, patients’ narratives Relate, diagnose and treat Qualitative, ethnomethodology, hermeneutic phenomenology 28 7 Hennius, B. J. (2013) [ 27 ] UK Contemporary chiropractic practice in the UK: a field study of a chiropractor and his patients in a suburban chiropractic clinic chiropractic Patients’ narratives, traditional knowledge, patients’ bodies, intuition, biomedicine Diagnose and treat, legitimise, educate and inform Ethnography 29 8 Ho, E.Y. & Bylund, C.L.…”
Section: Resultsmentioning
confidence: 99%
“…The studies indicated that CM practitioners were often guided by the preferences and values expressed by their patients. Stories shared by patients were noted as sources of knowledge in seven papers [ 21 , 24 , 25 , 27 , 30 , 31 , 37 ]. These were collected via patients’ self-reports (verbal or written) and based on accumulated understanding of the patients’ histories over time [ 21 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, three-quarters of chiropractors (76 %) believed that encouragement of maintaining normal activities, even in the presence of pain due to acute whiplash, was important to recovery [ 50 ]. Similarly, care delivered in individual chiropractic practices in the UK [ 53 ] and Northeastern Spain [ 54 ] were generally aligned with best practice. Two articles reported that a majority of clinicians in private practice used treatment not supported by current recommendations on nutrition [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that patients’ expectations about being given advice about managing symptoms were largely met. In another study involving chiropractic patients, the researcher found that patients had an inaccurate or rudimentary understanding of the mechanisms that underpin chiropractic treatment, were not particularly interested in how it worked and despite the explanations of the chiropractor, patients showed only a limited understanding of the mechanisms [ 11 ]. In our study more than 90% expected to be given information about chiropractic and what it involved and to be given a diagnosis and rationale for their treatment.…”
Section: Discussionmentioning
confidence: 99%